A Retrospective Feasibility Study of Salvage Pelvic Nodal Radiation in 6 Patients With Biochemical Failure Following Prostate Fossa Radiation: An Alternative to Androgen Deprivation Therapy (ADT). (October 2016) - Symon, Zvi; Ben-Bezalel, Guy; Spieler, Ben; Tsvang, Lev; Alezra, Dror; Berger, Raanan; Dotan, Zohar; Lawrence, Yaacov R.; Goldstein, Jeffrey
Abstract : Purpose: To evaluate salvage pelvic nodal radiation as an alternative to androgen deprivation therapy (ADT) in patients with biochemical failure and lymph node recurrence following salvage prostate fossa radiation. Methods: Six patients with biochemical failure and lymph node recurrence following prostate fossa radiation were treated with salvage pelvic nodal radiation therapy. A gross target volume was contoured using Choline PET/CT, CT, or MRI imaging. The clinical target volume included pelvic nodes. Avoidance structures were created using isodose lines from previous prostate fossa radiation plans. Radiation was delivered using IMRT or VMAT techniques. Failure was defined as a confirmed rise of prostate-specific antigen (PSA) over 0.2 ng/mL. Results: Four patients had presalvage PSA values <1 and 2 patients had PSAs >1. Dose to the clinical target volume was 54 to 60 Gy. The gross target volume dose was 60 to 73.6 Gy. One of the 2 patients with a high PSA received 6 months of concomitant ADT. Mean follow-up after RT for all patients was 24.9 months (range, 18.1 to 33.0 mo). All 5 patients with no ADT had significant PSA responses. PSA reduction was 80% (62% to 100%) of pre-RT PSA. At last follow-up, 2 patients with initial PSA<1 ng/mL remain free of biochemical progression at 33 and 20 months. Four patients have had PSA rise and meet criteria for failure. This included both patients with initial PSA values > 1. Duration of response before failure was 18.1 to 30.7 months. ADT for failure has been started in 1 patient. There was no grade ≥2 GI or GU toxicity. Conclusions: Salvage lymph node irradiation for patients with early biochemical recurrence and radiologic evidence of pelvic nodal metastases is well tolerated and associated with a durable biochemical response and may be an alternative to or may delay the need for ADT in some patients.